Depleted hydrocarbon reservoirs and CO2 injection wells –CO2 leakage assessment (Rudarsko-geološko-naftni zbornik, 2017)
Migration risk assessment of the injected CO2 is one of the fi rst and indispensable steps in determining locations for the implementation of projects for carbon dioxide permanent disposal in depleted hydrocarbon reservoirs. Within the phase of potential storage characterization and assessment, it is necessary to conduct a quantitative risk assessment, based on dynamic reservoir models that predict the behaviour of the injected CO2, which requires good knowledge of the reservoir conditions. A preliminary risk assessment proposed in this paper can be used to identify risks of CO2 leakage from the injection zone and through wells by quantifying hazard probability (likelihood) and severity, in order to establish a risk-mitigation plan and to engage prevention programs. Here, the proposed risk assessment for the injection well is based on a quantitative risk matrix. The proposed assessment for the injection zone is based on methodology used to determine a reservoir probability in exploration and development of oil and gas (Probability of Success, abbr. POS), and modifi ed by taking into account hazards that may lead to CO2 leakage through the cap rock in the atmosphere or groundwater. Such an assessment can eliminate locations that do not meet the basic criteria in regard to short-term and long-term safety and the integrity of the site.